The role of vascularization on changes in ligamentum flavum mechanical properties and development of hypertrophy in patients with lumbar spinal stenosis - Jezek, Jakub; Sepitka, Josef; Daniel, Matej; Kujal, Petr; Blanková, Alžběta; Waldauf, Petr; Krbec, Martin; Dousa, Pavel; Skala-Rosenbaum, Jiri; Samal, Filip; Jirasek, Tomas (The spine journal, 2020)
BACKGROUND CONTEXT: Ligamentum flavum (LF) induced lumbar spinal stenosis (LSS) is conditioned not only by its "gathering" but especially by hypertrophy. Previous studies have examined the pathophysiology and biochemical changes that cause the hypertrophy. Some studies have described a link between chronic LF inflammation and neovascularization but others have reported highly hypovascular LF tissue in LSS patients. Currently, there is no practical application for our knowledge of the pathophysiology of the LF hypertrophy. Considerations for future treatment include influencing this hypertrophy at the level of tissue mediators, which may slow the development of LSS. To our knowledge, there is no study of micromechanical properties of native LF to date. PURPOSE: (1) To clarify the changes in vascularization, chondroid metaplasia, and the presence of inflammatory cell infiltration in LF associated with LSS. (2) To quantify changes in the micromechanical properties associated with LF degenerative processes. STUDY DESIGN/SETTING: Vascular density analysis of degenerated and healthy human LF combined with measurement of micromechanical properties. METHODS: The study involved 35 patients who underwent surgery between November 1, 2015 and October 1, 2016. The LSS group consisted of 20 patients and the control group consisted of 15 patients. LF samples were obtained during the operation and were used for histopathological and nanoindentation examinations. Sample vascularization was examined as microvascular density (Lv), which was morphometrically evaluated using semiautomatic detection in conjunction with NIS-Elements AR image analysis software. Samples were also histologically examined for the presence of chondroid metaplasia and inflammation. Mechanical properties of native LF samples were analyzed using the Hysitron TI 950 TriboIndenter nanomechanical testing system. RESULTS: Vascular density was significantly lower in the LSS group. However, after excluding the effect of age, the difference was not significant. There was high association between Lv and age. With each increasing year of age, Lv decreased by 11.5 mm2. Vascular density decreased up to the age of 50. Over the age of 50, changes were no longer significant and Lv appeared to stabilize. No correlation was observed between Lv and the presence of inflammation or metaplasia; however, LSS patients had a significantly increased incidence of chondroid metaplasia and inflammatory signs. The mechanical properties of control group samples showed significantly higher stiffness than those samples obtained from the LSS group. CONCLUSION: This study showed that Lv changes were not dependent on LSS but were age-dependent. Vascular density was found to decrease up to the age of 50. A significantly higher incidence of chondroid metaplasia and inflammation was observed in LSS patients. The mechanical property values measured by nanoindentation showed high microstructural heterogeneity of the tested ligaments. Our results showed that healthy ligaments were significantly stiffer than LSS ligaments. CLINICAL SIGNIFICANCE: Prevention of the loss of LF vascularization during aging may influence stiffness of LF which in turn may slow down the LF degenerative processes and delay onset of LSS.
Keywords: Hypertrophy; Spinal Stenosis; lidé; Lumbar Vertebrae; Ligamentum Flavum; bederní obratle; hypertrofie; Humans; ligamentum flavum; spinální stenóza